The Association Between High and Unnecessary Antibiotic Prescribing: A Cohort Study Using Family Physician Electronic Medical Records. (12th August 2020) - Kitano, Taito; Langford, Bradley J; Brown, Kevin A; Pang, Andrea; Chen, Branson; Garber, Gary; Daneman, Nick; Tu, Karen; Leung, Valerie; Candido, Elisa; Wu, Julie Hui-Chih; Hwee, Jeremiah; et al.
Abstract: Background: Approximately 25% of outpatient antibiotic prescriptions are unnecessary among family physicians in Canada. Minimizing unnecessary antibiotics is key for community antibiotic stewardship. However, unnecessary antibiotic prescribing is much harder to measure than total antibiotic prescribing. We investigated the association between total and unnecessary antibiotic use by family physicians and evaluated inter-physician variability in unnecessary antibiotic prescribing. Methods: This was a cohort study based on electronic medical records of family physicians in Ontario, Canada, between April 2011 and March 2016. We used predefined expected antibiotic prescribing rates for 23 common primary care conditions to calculate unnecessary antibiotic prescribing rates. We used multilevel Poisson regression models to evaluate the association between total antibiotic volume (number of antibiotic prescriptions per patient visit), adjusted for multiple practice- and physician-level covariates, and unnecessary antibiotic prescribing. Results: There were 499 570 physician–patient encounters resulting in 152 853 antibiotic prescriptions from 341 physicians. Substantial inter-physician variability was observed. In the fully adjusted model, we observed a significant association between total antibiotic volume and unnecessary prescribing rate (adjusted rate ratio 2.11 per 10% increase in total use; 95% CI 2.05–2.17), and none of the practice- and physician-level variables were associated with unnecessary prescribing rate. Conclusions: We demonstrated substantial inter-physician variability in unnecessary antibiotic prescribing in this cohort of family physicians. Total antibiotic use was strongly correlated with unnecessary antibiotic prescribing. Total antibiotic volume is a reasonable surrogate for unnecessary antibiotic use. These results can inform community antimicrobial stewardship efforts. Abstract : We identified a strong correlation between total and unnecessary antibiotic prescribing among family physicians, which could not be explained by other practice or physician characteristics. These data suggest that total antibiotic prescribing is an appropriate surrogate for unnecessary use.